2005
DOI: 10.1007/s00262-005-0686-1
|View full text |Cite
|
Sign up to set email alerts
|

A DeImmunized chimeric anti-C3b/iC3b monoclonal antibody enhances rituximab-mediated killing in NHL and CLL cells via complement activation

Abstract: Complement-dependent cytotoxicity (CDC) is a key mechanism of Rituximab (RTX) action in killing non-Hodgkin's lymphoma (NHL) cells both in vitro and probably in vivo. A DeImmunized, mouse/human chimeric monoclonal antibody (Mab), H17, specific for cell-associated complement C3 cleavage products, C3b and iC3b, was generated to enhance RTX-mediated killing of target cells by CDC. When NHL cell lines were treated with RTX and H17 in the presence of complement for 1 h, there was 40-70% more cell death than that ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
7
1
1
Order By: Relevance
“…31 Further, using primary cells isolated from non-Hodgkin lymphoma and chronic lymphocytic leukemia patients, it was shown that a mouse-human chimeric mAb specific for C3b and iC3b enhanced rituximab-mediated CDC ex vivo. 32 In contrast to the current study using CR2Fc, however, there are no reports of anti-iC3b enhancing the therapeutic efficacy or outcome of mAb therapy in terms of tumor burden or survival in an in vivo model. It is also significant that CR2Fc recognizes the C3 activation products iC3b, C3dg, and C3d, whereas analysis of the anti-iC3b mAb used in the aforementioned studies revealed specificity for C3b and iC3b.…”
Section: Discussioncontrasting
confidence: 57%
“…31 Further, using primary cells isolated from non-Hodgkin lymphoma and chronic lymphocytic leukemia patients, it was shown that a mouse-human chimeric mAb specific for C3b and iC3b enhanced rituximab-mediated CDC ex vivo. 32 In contrast to the current study using CR2Fc, however, there are no reports of anti-iC3b enhancing the therapeutic efficacy or outcome of mAb therapy in terms of tumor burden or survival in an in vivo model. It is also significant that CR2Fc recognizes the C3 activation products iC3b, C3dg, and C3d, whereas analysis of the anti-iC3b mAb used in the aforementioned studies revealed specificity for C3b and iC3b.…”
Section: Discussioncontrasting
confidence: 57%
“…infusion of rituximab in a cynomolgus monkey model. A subsequent study by Peng et al (26) showed that a mouse/ human chimeric mAb specific for C3b and iC3b enhanced rituximabmediated killing of non-Hodgkin's lymphoma cell lines and cells isolated from non-Hodgkin's lymphoma and chronic lymphocytic leukemia patients. There is a significant potential advantage of CR2-Fc over anti-iC3b mAbs, as evidenced by its ability to significantly increase long-term survival of mice receiving mAb therapy; in the presence of serum, the initial covalently bound complement activation product C3b is very rapidly degraded to iC3b, which is in turn fairly rapidly degraded to the long-lived fragments C3dg and then C3d.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has previously been shown to enhance CDC of lymphoma cell lines in vitro and to increase deposited complement when coadministered with rituximab in a cynomolgus monkey model. 3,4 Imai et al have previously introduced CR2-Fc, a fusion protein between the extracellular domain of the complement receptor 2 (CR2) and an IgG Fc domain. In contrast to antiiC3b antibodies CR2 also recognizes C3d and C3dg, the relatively long-lived complement degradation fragments.…”
Section: Boosting Antibody Therapy With Complement ------------------mentioning
confidence: 99%
“…3 In clinical trials, sorafenib has shown promising results either as a monotherapy or when combined with standard chemotherapy, with complete remissions (CRs) seen in some FLT3-ITD patients. 4 Despite the promise of sorafenib as an agent with activity against FLT3-ITD, there are many potential limitations, including initial inherent resistance to FLT3 inhibitors due to concurrent downstream pathway activation, and emergence of mutations during therapy that reduce inhibition or prevent drug binding. 2 Another important mechanism is the up-regulation of antiapoptotic Bcl-2 family members.…”
Section: Boosting Antibody Therapy With Complement ------------------mentioning
confidence: 99%